Students’ Perception of Using Group Work Method in English Class: A Gender-Based Comparative Study at a Senior High School in North Minahasa - Juinsi Suily Tumbol; Virginia Gabrella Sengkey (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
This study investigated students’ perceptions of the benefits of group work in English classes, their level of preference for this learning method, and how frequently teachers apply it during instruction. It also examined whether students’ perceptions differ significantly based on gender. A descriptive and comparative research design was employed, using a questionnaire adapted from Daba et al (2017), as well as Hung and Mai (2020). A convenience sampling technique was used to select 77 eleventh-grade students (31 male and 46 female) from a private high school in North Minahasa, Indonesia. The findings indicate that students generally view group work positively and recognize its benefits in English learning. In addition, students reported a high preference for using group work in class, and teachers were found to implement the method at a high level. The study also revealed a significant gender difference: male students showed a stronger preference for group work and participated more actively than female students. This difference was statistically significant (t(75) = -3.67, p < .001) and represented a medium-to-large effect (Cohen’s d = 0.78). Based on these results, teachers are encouraged to consider gender-related participation patterns when applying group work strategies. Practically, the findings suggest that teachers should adopt gender-responsive grouping practices, such as balanced role assignment and structured turn-taking, so that both male and female students participate and benefit equally from collaborative English learning. Future research is recommended to explore additional factors influencing group work effectiveness and its impact on students’ English proficiency